Educational Need In The Rainbow Troops By Andrea Hirata (2009): A Humanistic Psychological Approach - Triono, Agus; , Drs. Abdillah Nugroho, M. Hum; , Titis setyabudi, S. S. M. Hum (2013)
The major issue of this study is how is the educational need reflected in Andrea Hinata novel The Rainbow Troops: a humanistic psychological approach. The objective of this study is to analyze The Rainbow Troops novel based on its structural elements that help the writer identify the narrative aspect and technical element of the major character and to analyze the educational need in The Rainbow Troops novel by Andrea based on humanistic psychological perspective. The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. The data collection method is library research by collecting both primary and secondary data. The data analysis method is descriptive qualitative analysis based on psychoanalytic approach. The results of the study show; firstly, it is about structural analysis of The Rainbow Troops novel. The setting of place and time was suitable with the theme of the novel, where usually people from a small village have a lower education rather than the people from town. It is suitable with the theme of the novel "The education is one of people's rights on their life". Secondly, Educational needs of Ikal is showed by the believe of Ikal and his people in Belitong on the modern medicine. With the spirit coming from Bu Mus, he believes that he can save the people's life from stupidity. Self-Esteem Needs of Ikal, where Ikal as a boy, absolutely really want to satisfy him self with something he likes. Ikal feels satisfy with the way Pak Harfan teaches. As a kid in a small village, they always do a lot of things to satisfy them self, like playing together and also made foolish bets together. Self-Actualization Needs on the end of the story of Rainbow Troops, Finally Ikal success and he gets what he wants as a student in a foreign country.